Effectiveness of School Operational Assistance Program Implementation at SD Inpres Dekai, Yahukimo - Evy Marlyn Saalino (Budapest International Research and Critics University, 2021)
The objective of this study was to find out the effectiveness of the implementation and the inhibiting factors for the implementation of the School Operational Assistance (BOS) program at SD Inpres Dekai, Yahukimo Regency. The research used a mixed-method, namely using both qualitative and quantitative data. The qualitative data were obtained through in-depth interviews with informants who were members of BOS management at SD Inpres Dekai, including the person in charge and team members, teachers who were not BOS management members, education observers, community elements, and school committees. Meanwhile, the quantitative data were obtained from the Ministry of Education and Culture. The results of the research showed that the implementation of the BOS program at SD Inpres Dekai was generally considered ineffective based on input, process, and output factors. On the one hand, the results of this research showed that the objectives of the BOS program at SD Inpres Dekai had been achieved. On the other hand, however, there were still many things to be improved in terms of the process, such as involving student parents as the BOS management team members, conducting socialization, and synchronizing student data at Dapodikdasmen. The inhibiting factors for the implementation of the BOS program at SD Inpres Dekai are also shown ini the results of this study.